PENGARUH PERSEPSI DAN MOTIVASI TERHADAP MINAT MAHASISWA PROGRAM STUDI PERPAJAKAN UNTUK BERKARIR DI BIDANG PERPAJAKAN (Studi pada mahasiswa Fakultas Ilmu Administrasi Universitas Brawijaya) - Dayshandi, Dody (Jurnal Mahasiswa Perpajakan, 2015)
The income from tax sectors have the largest portion of state revenue, because the target of tax revenue also increase each year. The numbers of taxpayers are bigger than the number of tax officials, it needs to increase additional number of tax officials, both are from government or company. The additional of tax officials must be balanced with a professional attitude of tax official candidates, then the function of tax officials can be realized well. The purpose of this research is to understand the influence of simultaneously and partial of perception also motivation toward students’s interest of taxation department to have career in taxation field (study on students of the Faculty of Administrative Science of Brawijaya University). Kind of this research is descriptive research with quantitative  method. The population in this research from taxation class students of 2010 till 2013. Technique sampling was using non-probability technique sampling and proportional stratified random sampling, with 90 people as respondent. Analysis method was using multiple linear regression analysis and descriptive statistic. Based on the results of simultaneous test, there were simultaneous influences between perception and motivation variables for students’s interest of taxation to have career in taxation field. The results of t test, there were partial influences on perception and motivation variables for students’s interest of taxation to have career in taxation field. Suggestions for the Faculty are to provide training of tax software programs, for examples zahir and e-SPT application. Suggestions for students are trying to know their capabilities and interests, and always following all of taxation training programs, in order to give another skill in taxation field. Keywords: Perception, Motivation, Interest, Taxation Career